Design of a Fluidized Bed Bio Film Reactor for Wastewater Treatment: Optimizing wastewater treatment using a Fluidized Bed Biofilm Reactor (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Fluidized Bed Biofilm Reactor (FBBR) can be an efficient alternative solution in advanced waste water treatment processes. FBBR process can reduce production of sludge in water treatment and also offers lower hydraulic retention time compared to other biological and chemical processes. The basic concept of the process consists of passing wastewater up through a packed bed of particles at a velocity sufficient to fluidize the particles. FBBR combines the best features of activated sludge and trickling filtration into one process. The design calculations have been done based on literature and some collective assumptions, from work it can be summarised that minimum fluidisation velocity for 50 MLD is 0.12msec. and the calculated Reynolds number show that, the fluidization to be a laminar fluidization.